Effect of electrode distance in electrocoagulation process to treat restaurant wastewater - Nazihan, Mat Yaman (2019)
Electrocoagulation treatment process (EC) is an effective ttreatment process that applying an electric current to enhance the oxidation and reduction take place.This project is all about the effect of operating parameters on restaurant wastewater treatment by using electrocoagulation method. In general, wastewater is all the dirty water comes from main sources either schools, restaurants, commercial establishments, hospitals, farms and factory that usually flow down enters storm drainage system. Oily and greasy wastewater from restaurant or canteen cannot be collected and discharged to municipal drainages system directly because of faultiness of the existing wastewater treatment system. Thus, in this project, the treatment of restaurant wastewater by investigate, and measure by testing the level of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS). In this project, only one of the three main operating parameters have been investigated and come out with the results. The operating parameter that involve is the effect of electrode distance on restaurant wastewater treatment by electrocoagulation process has been successfully observed and investigated.